2015
DOI: 10.1007/s10479-015-1811-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and improvement of employee job-satisfaction: a full-scale implementation of MUSA methodology on newly recruited personnel in a major French organisation

Abstract: During the last 20 years, a large number of studies have investigated the relationship between employee satisfaction and specific job characteristics, with often contradictory results. The aim of this paper is the assessment of job satisfaction of recent recruits in a large French company. The approach adopted here is to view employees as internal customers of an organization, and their satisfaction as an important driver for business success. Using the MUSA multicriteria methodology for customer satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Job satisfaction is one frequently monitored factor at work, particularly at a time of high demand for labour on the labour market when it is very easy to change employer (Gosse & Hurson, 2016). Satisfied personnel are a major driver of an organization (Rani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction is one frequently monitored factor at work, particularly at a time of high demand for labour on the labour market when it is very easy to change employer (Gosse & Hurson, 2016). Satisfied personnel are a major driver of an organization (Rani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…and accommodation level, administration, work condition, recognition, co-workers communications, educational activity, payment, vacation, and leaves are used to determine the job satisfaction to the nurses of Al-Qassim hospital of Sudia Arabia[36]. The research used the MUSA method that showed the richness of the set of factors which determine the satisfaction of newly recruited personnel at work in a large French organization[37].Martin & Kaufman (2013) investigated that there is a strong positive correlation between organizational climate and the dependent variable of job satisfaction in South African Information & Technological organization. Work employment, Employee relationship, and training influence on job satisfaction of Bangladesh government Sonali Bank's employees [38].…”
mentioning
confidence: 99%
“…MUSA outputs are filled with information from a managerial perspective, revealing which dimensions need more improvement and their respective priorities. Thus, they should be within the managers' grasp to improve their performance (Gosse and Hurson, 2016). Compared with other alternatives, the low utilization of MUSA in healthcare and its potential generates opportunities for a broader diffusion of studies using this method (Ferreira et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This method assumes a set of features of the evaluated product or service, according to which customers perceived their satisfaction. These characteristics are the method's input (Gosse and Hurson, 2016).…”
Section: Introductionmentioning
confidence: 99%